(untitled) (University Journal of Zoology, Rajshahi University, 2013)
Effectiveness of diatomaceous earth (DE) and other inert dusts (kaolin powder, paddy husk ash, coal ash, alluvial soil, china clay) and a dust formulation insecticide carbaryl have been tested on the pulse beetles Callosobruchus chinensis L. and C. maculatus (F.). The bioassay of the dusts was done on adult beetles by mixing them with normal food (lentil and black gram seeds). The LD50 of the combined doses of mixtures for C. chinensis have been calculated as 12703.57 and 859.36 ppm for DE+ kaolin powder; 2432.78 and 274.00 ppm for DE+ paddy hush ash; 3430.036 and 426.16 ppm for DE+ coal ash; 12563.47 and 652.29 ppm for DE+ alluvial soil; 2242.81 and 325.76 ppm for DE+ china clay; and 21.33 and 14.45 ppm for DE+ carbaryl after 24 and 48 h after treatment respectively. The LD50 of combined doses of different mixtures for C. maculatus have been calculated as 3640.65 and 503.74 ppm for DE+ kaolin powder; 54946.68 and 987.2394 ppm for DE + paddy hush ash; 61029.04 and 3229.436 ppm for DE+ coal ash; 61029 and 4265.599 ppm for DE+ alluvial soil; 4648.786 and 642.278 ppm for DE+ china clay; and 24.12017 and 15.47023 ppm for DE+ carbaryl after 24 and 48 h after treatment respectively. The co-toxicity coefficient has been calculated and all ratios showed synergistic action. The highest co-toxicity coefficient was recorded as 88885.15 and 92107.22 in DE+ carbaryl at 24 and 48 h after treatment for C. chinensis and 78615.55 and 86004.88 in DE+ carbaryl at 24 and 48 h after treatment for C. maculatus. DOI: http://dx.doi.org/10.3329/ujzru.v31i0.15436 Univ. j. zool. Rajshahi Univ. Vol. 31, 2012 pp. 73-78